A century of anthropogenic river alterations in a highly diverse river coastal basin: Effects on fish assemblages - Moraga, Diego; Vivancos, Aurélien; Ruiz, Víctor H.; Rojas, Octavio; Díaz, Gustavo; Manosalva, Aliro; Vega, Paulina; Habit, Evelyn (Frontiers in Environmental Science, 2022)
The global increase in human population is driving a continuous conversion of land to anthropogenic uses. This is a major threat to lotic ecosystems worldwide, as it compromises the biotic integrity and health of rivers and streams. Studies in the northern hemisphere have shown that the effects of urbanization on fish assemblages include decrease and/or loss of diversity and abundance of native species, and a proliferation of tolerant exotic species. Such effects have not been widely studied in developing countries like Chile, where urbanization has impacted several river ecosystems. Over decades, the lower zone of the Andalién River in Central Chile has gone over intense non-planned urbanization stemming from the city of Concepción, leading to several physical alterations. The native fish and lamprey fauna of this coastal river basin has been reported as very diverse, with a total of 16 native species. However, this fauna has been affected by multiple effects of different land uses and direct alterations in the riverbed. To study how these fish and lamprey assemblages have changed, this paper compiles records from 1919 to 2018 and analyzes them in relation to the direct and indirect anthropogenic alterations in the basin. The results show a significant reduction in richness and abundance of native species, with only nine species currently. The two migratory lampreys, one of them endemic (Mordacia lapicida), have been extirpated from the Andalién River basin. Conversely, the richness and distribution of introduced species has increased throughout the river basin. The invasive species Gambusia holbrooki, first registered in 1999, is currently the most abundant in the urban zone of the river. Although the more substantial direct alterations of the riverbed occurred in the lower areas, a steeper reduction in native species richness occurred in the middle areas subjected to a long history of agricultural and forestry land use. We suggest the loss of resilience of the river ecosystem, and that the collapse of biodiversity in this river system demonstrates the lack of urban planning and the inefficiency of environmental regulations in protecting native species and ecosystems with high conservation value in Chile.